Early Everolimus Initiation Fails to Counteract the Cytotoxic Response Mediated by CD8+ T and NK Cells in Heart Transplant Patients - Díaz-Molina, Beatriz; Diaz-Bulnes, Paula; Carvajal Palao, Reyes; Bernardo, Maria José; Rodriguez, Ramón M.; Corte-Iglesias, Viviana; Moris de la Tassa, Cesar; Lambert, Jose Luis; Suarez-Alvarez, Beatriz (Frontiers in Immunology, 2018)
The positive long-term effects of conversion to everolimus (EVL) after heart transplantation (HT) have been evaluated in several studies. However, the timing of EVL initiation, the best way to combine it with other immunosuppressive treatments, and the impact of these combinations on the immune response are poorly understood aspects. Here, we analyzed the immune phenotype and function of HT patients (n=56) at short and long terms (prospective and retrospective cohorts), taking into account the time of EVL initiation: early (3 months post-transplant, EVL-E group) or late (>1 year post-transplant, EVL-L group) compared with mycophenolate mofetil treatment (MMF group). We show that early EVL conversion from MMF allows the increase of cytotoxic (CD56dim CD16+) NK and effector-memory (EM, CD45RA- CCR7-) CD8+ T cell subsets, which show a significantly higher level of expression of cytotoxic molecules, IFN-γ production and degranulation ability under activation. NK cell expansion is accompanied by an altered balance of receptor expression, increasing the activation state and lytic activity of those cells. Those changes are detected after as little as 1 month after EVL conversion in association with the expansion of regulatory T cells and the decrease in B cell frequency. However, no changes in the immune cells subsets were observed after late EVL initiation (EVL-L) compared with the MMF group. Our results imply that only early EVL conversion induces key changes in the post-transplant immune response, preserving an efficient anti-viral response, but simultaneously showing a limited ability to counteract the cytotoxic response to the allograft.